2006
DOI: 10.1016/j.transproceed.2006.10.161
|View full text |Cite
|
Sign up to set email alerts
|

An MHC Class II Disparity Raises the Threshold for Tolerance Induction in Pulmonary Allografts in Miniature Swine

Abstract: Objectives-The mechanisms and treatment of chronic rejection in pulmonary allotransplantation remain elusive. We have induced robust tolerance to class I-disparate lung allografts in miniature swine using an intensive 12-day course of tacrolimus. Here, we test whether a tolerant state can be induced in swine receiving fully mismatched lung allografts.Methods-Orthotopic left lung allografts were performed using MHC class I-disparate (Group 1: n = 3) or fully disparate (Group 2: n = 6) donors. The recipients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Graft survival data compiled as follows: kidney alone (38), lung alone (39), heart alone (40), heart and kidney (40). …”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graft survival data compiled as follows: kidney alone (38), lung alone (39), heart alone (40), heart and kidney (40). …”
Section: Key Pointsmentioning
confidence: 99%
“…Long term tolerance was easily induced in renal allografts (38), whereas lung survival ranged from 100 to >500 days (39) and hearts only survived 18-35 days (40)(Fig 1). …”
Section: Introductionmentioning
confidence: 99%
“…In another earlier study, five of six lung transplant recipients demonstrated donor-specific hyporesponsiveness postoperatively; animal no. 15616 demonstrated antidonor responsiveness on day of lung rejection (POD 103, group 3, Table 1) (12). Of note, one heart recipient (no.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of a 12-day course of calcineurin inhibition prolonged class I and full MHC-mismatched heart allograft survival slightly; however, all grafts rejected by postoperative day (POD) 55 (8,9). In contrast, calcineurin inhibition can lead to tolerance of class I and full MHC-mismatched kidney allografts (10,11), as well as full MHC-mismatched lung allografts (12). …”
Section: Introductionmentioning
confidence: 99%
“…Using MHC class I disparate inbred miniature swine, Shoji et al demonstrated that a 12 day post-operative course of continuous intravenous tacrolimus without further immunosuppression resulted in long term lung graft survival without evidence of chronic rejection [87]. This was followed by a study with full MHC disparity with similar graft longevity, but some evidence of OB on pathology [88]. A recent development in the prevention of OB includes the use of mesenchymal stem cells.…”
Section: Lung Transplant Tolerancementioning
confidence: 99%